Impact of sensor design on the contactless inspection of planar electronic devices by capacitive coupling - Koerdel, M.; Alatas, F.; Schick, A.; Rupitsch, Stefan; Lerch, Reinhard (Elsevier BV, 2011)
The impact of sensor design on the inspection of planar electronic devices by capacitive coupling is investigated. To allow for the inspection of electrically isolated conductive parts of devices, such as partly processed flat panel displays or printed electronic circuits, new sensor designs have been developed and are evaluated with the help of finite element simulations. The analysis of the simulation results shows that a clear detection of the conductive parts is achieved if the sensor geometry enforces a non-uniform electrical field distribution in the range of the sensor area. By studying the capacitive coupling to the individual parts of the sensors, design rules for sensor electrode and shielding geometry are deduced. (C) 2011 Published by Elsevier Ltd.
Keywords: capacitive coupling; contactless inspection; finite element (FE) simulation; flat panel display (FPD); planar electronic device; sensor design